ROMANIA’S ECONOMIC RESTRUCTURING MUST BE EFFECTED BEFORE EURO ADOPTION - CIOBANU , Andreea Maria (Journal of Advanced Studies in Finance; Vol 6 No 1 (2015): JASF Volume VI, Issue 1(11), Summer, 2015, 2016)
AbstractThe fact that Romania has met all nominal criteria stipulated in Maastricht Treaty for the adoption of the euro for the firstsince June 2014, including inflation and presented quite well the criteria for real convergence towards the euro area, does not mean there is no long term risks that can damage this situation.The authorities’ established date of January 1, 2019 for the adoption of the euro is an ambitious objective and therefore structural problems and competitiveness must be the top priority of any government because the economy has no political colour, being neither left nor right.From these brief considerations in this article we propose, based on analysis and calculations, to evaluate Romania's chances to meet the target and at the same time, to suggest some directions for Romania to avoid the mistakes of other countries that have entered less prepared in the euro area and adopt the euro at the appropriate time with minimum risk and maximum benefit given the need for sustainable nominal convergence criteria besides ensuring increased competitiveness in support of a sustainable real economic growth.